2008
DOI: 10.2214/ajr.07.3034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and MRI Findings Associated with False-Positive Knee MR Diagnoses of Medial Meniscal Tears

Abstract: False-positive MR diagnoses of medial meniscal tears are more common for longitudinal tears than other tear types and are also more common with MR abnormalities at either the superior surface or the meniscocapsular junction. Spontaneous healing of longitudinal tears accounts for some false-positive MR diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 19 publications
1
29
0
5
Order By: Relevance
“…14 De Smet et al 15 have previously reported on a highfalse positive rate of medial meniscus (MM) tears with MRI due to spontaneous healing of longitudinal tears. However, other studies have reported a high falsenegative rate with MRI and a low sensitivity.…”
mentioning
confidence: 99%
“…14 De Smet et al 15 have previously reported on a highfalse positive rate of medial meniscus (MM) tears with MRI due to spontaneous healing of longitudinal tears. However, other studies have reported a high falsenegative rate with MRI and a low sensitivity.…”
mentioning
confidence: 99%
“…The third shortcoming of our study is that reports of the arthroscopic surgery were not available for some of our patients, so we could not relate the arthroscopic findings for all the patients' to their MRI. However, although the use of arthroscopy is the gold standard for detecting the presence of a meniscal tear [20,24], MR images also have good sensitivity (81% to 97%) and specificity (88% to 86%) for diagnosing meniscal tears [25]. Arthroscopy alone is not a good technique for detecting meniscal cysts and its communication with meniscal tear because of low sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Además, una tasa alta de falsos positivos se ha informado de fisuras longitudinales del cuerno posterior MM, posiblemente secundaria a la visualización incompleta de la periferia lejana del MM en la artroscopia o por la curación espontánea [23].…”
Section: Planteamiento Del Problemaunclassified